Recent Applications of Continuous Flow in Homogeneous Palladium Catalysis - Markovič, Martin; Lopatka, Pavol; Gracza, Tibor; Koóš, Peter (Synthesis, 2020)
Considerable advances have been made using continuous flow chemistry as an enabling tool in organic synthesis. Consequently, the number of articles reporting continuous flow methods has increased significantly in recent years. This review covers the progress achieved in homogeneous palladium catalysis using continuous flow conditions over the last five years, including C–C/C–N cross-coupling reactions, carbonylations and reductive/oxidative transformations.1 Introduction2 C–C Cross-Coupling Reactions3 C–N Coupling Reactions4 Carbonylation Reactions5 Miscellaneous Reactions6 Key to Schematic Symbols7 Conclusion
Keywords: flow chemistry; homogeneous catalysis; palladium; cross-coupling; Buchwald–Hartwig; carbonylation; oxidation; reduction